Group Dynamics in Multicultural Group Counseling - Ristianti, Dina Hajja (Unib Press, 2023)
Group dynamics are important in multicultural group counseling. Group leaders can create an inclusive and supportive environment for group members to broaden their understanding of diversity, and improve collective psychological well-being. This research is qualitative research where researchers are directly involved in group counseling activities. Members of the group consist of 10 people of various ethnicities. Data were taken through interview and observation techniques and analyzed using inductive analysis techniques. The results showed that group dynamics in multicultural group counseling can be carried out at the early stage, transition stage, activity stage, and termination stage. Group leaders must improve their multicultural ability to overcome obstacles in the implementation of multicultural group counseling by adding insight related to cultural values and diversity of light games that can accommodate the cultural diversity of group members.